Pengaruh E-Modul Flipbook Web Berbasis Problem Based Learning Terhadap Pengetahuan Faktual, Konseptual dan Prosedural Pada Materi Daur Hidup Hewan di Kelas IV Sekolah Dasar - Afifah Qumariah; Endang Widi Winarni; Osa Juarsa (UNIB Press, 2026)
This study aimed to examine the impact of a Problem-Based Learning (PBL)–based Web Flipbook E-Module on fourth-grade students’ factual, conceptual, and procedural knowledge regarding the animal life cycle. Using a quasi-experimental nonequivalent control group design, quantitative data were collected through essay tests. The findings indicate that the integration of PBL supported by the e-module significantly enhanced all three types of knowledge. For factual knowledge, the experimental class achieved an average score of 93 compared to the control class’s 86, with Fcount 14.985 > Ftable 2.98 and an N-gain of 0.65 (medium), exceeding the control’s 0.46. Conceptual knowledge also improved, with the experimental class scoring 70 versus 46 in the control class, supported by Fcount 11.203 > Ftable 2.98 and an N-gain of 0.56 (medium), higher than the control’s 0.28 (low). Procedural knowledge showed similar gains, with scores of 69 in the experimental class and 40 in the control class, along with Fcount 6.374 > Ftable 2.98 and an N-gain of 0.43 (medium), compared to 0.13 (low) in the control class. Regression analysis revealed a strong correlation (r = 0.796) among the three knowledge dimensions, confirming their interconnected contribution to students’ overall understanding. Overall, the PBL-based Web Flipbook E-Module proved effective in comprehensively enhancing students’ knowledge.